“Staka Woman Tumas”: An Examination of Police Perspectives on Gender-Balancing within the Royal Solomon Islands Police Force - Harry, Casandra (Women & criminal justice, 2024)
In countries emerging out of conflict, state-building initiatives tend to prioritize gender-balancing. Post-conflict police reform in the Solomon Islands aligned with this set standard, as capacity-building efforts within the Royal Solomon Islands Police Force (RSIPF) prioritized the empowerment, inclusion, and promotion of women within the force. Through the use of Interpretative Phenomenological Analysis (IPA) this study investigated, identified, and described common perceptions held by eighteen (18) officers about how they viewed gender reform in the RSIPF. The research found that although officers believed that gender-balancing was necessary, the increased inclusion of women conflicted with their traditional roles and positions and brought several challenges to the effective functioning of the force. It was also revealed that officers were of the view that the organization was not yet ready to fully embrace gender-balancing. The arguments presented herein further build on scholarly discussions about gender equality in policing organizations in small-island developing states in the Pacific.